Urgensi Nilai-Nilai Spiritualitas dalam Manajemen Pendidikan di Era Kecerdasan Buatan (AI) - Thoha, Mohammad (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
Managing education is about bringing together many people toward a common goal. There, we find shared characters and various dynamics. To unite these people requires a common determination and passion, based on honesty, integrity, and sincerity from all parties. This is the urgency of spiritual values ​​in educational management. This paper attempts to offer several practical steps and analyze the obstacles to integrating spiritual values ​​into educational management. Using a bibliographic approach combined with field facts, the author explores concepts and offers alternative approaches to educational management. Ultimately, the author finds that educational institutions are not profit-driven businesses. Likewise, educational actors (teachers, education personnel, and students) are not inanimate objects, like mechanical devices ready to be moved. They have feelings, empathy, need appreciation, and also need satisfaction from their work. The existence of alumni who contribute fully to community development is the pinnacle of their work success. Educational success is no longer measured by how high a grade is obtained, but by the extent to which alumni are useful in real life. This paper theoretically contributes to the development of educational management science, particularly in the field of human resource development. It also practically contributes to improving the quality of education in the field of developing human resources with character based on spiritual values.